Status Gizi dengan Kejadian Anemia pada Remaja: Literatur Review - Setianingsih, Lilis Zuniawati (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, 2023)
Objectives of this paper is to determine the relationship between nutritional status and the incidence of anemia in adolescents. The literature review study is a method used in collecting data or sources related to a particular topic that can be obtained from various sources such as journals, books, the internet, and other libraries. The article search stage uses the keyword